2001
DOI: 10.1161/hh1401.093458
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Locus in Mice That Blocks Development of Atherosclerosis Despite Extreme Hyperlipidemia

Abstract: Abstract-The genes contributing to the common forms of atherosclerosis are largely unknown. One approach to dissecting complex traits such as atherosclerosis is to use animal models, such as the mouse, to map and characterize the genetic loci involved. We now report the identification of a locus for aortic lesion formation on mouse chromosome 6 that exhibits a highly significant lod score of 6.7 in a genetic cross between the susceptible strain, C57BL/6J, and the resistant strain, CAST/Ei. The locus was confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
56
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 22 publications
4
56
0
1
Order By: Relevance
“…Moreover, resistance to atherosclerosis by the chromosome 6 congenic region or the 5LO knockout was mediated, in part, by bone-marrow-derived cells as judged by bone marrow transplantation experiments, consistent with a role for 5LO (Mehrabian et al 2001(Mehrabian et al , 2002. From this work, we concluded that 5LO is a primary candidate gene in the CON6 locus (Mehrabian et al 2002).…”
supporting
confidence: 68%
See 3 more Smart Citations
“…Moreover, resistance to atherosclerosis by the chromosome 6 congenic region or the 5LO knockout was mediated, in part, by bone-marrow-derived cells as judged by bone marrow transplantation experiments, consistent with a role for 5LO (Mehrabian et al 2001(Mehrabian et al , 2002. From this work, we concluded that 5LO is a primary candidate gene in the CON6 locus (Mehrabian et al 2002).…”
supporting
confidence: 68%
“…To generate chromosome 6 subcongenic Ldlr À/À mice, B6.CAST chromosome 6 congenic mice containing the lowdensity-lipoprotein-receptor null mutation (referred to here as ''CON6.Ldlr (Mehrabian et al 2001) …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Initially, Artles was identified in an F 2 cross between inbred strains C57BL/6J and CAST/Ei and exhibited a highly significant LOD score of 6.7 ( Figure 1B). 36 Interestingly, there was coincident linkage of insulin levels with this locus, raising the possibility that the underlying gene has pleiotropic effects on atherosclerosis and other related metabolic traits ( Figure 1B). Subsequently, a congenic strain was developed to confirm the functional importance of the QTL and to identify the underlying gene that causes resistance to lesion formation.…”
Section: Allayee Et Al Mice and Atherosclerotic Genetic Factorsmentioning
confidence: 99%